Evaluation of Limboto Lake Management Policy for Infrastructure Development - Jesica Febrila Taha; Muh. Firyal Akbar; Sri Lestari Gintulangi; Widya Kurniati Mohi (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2026)
Infrastructure development policy is a systematic process to assess the extent of effectiveness, efficiency, and impact of policies implemented in infrastructure development and management. This process involves an in-depth analysis of whether policy objectives have been achieved, whether the resources used have been optimized, and how the policy affects various aspects, such as community welfare, environmental sustainability, and regional economic development. The purpose of the study was to identify the lack of policy synchronization and coordination between related institutions and to identify the involvement of community participation around Limboto Lake. Research design: This qualitative study uses a descriptive research design. The sample of data sources used in qualitative research is still temporary. Informants to be used such as the Regional Government, River Basin Center (BWS), and Local Communities who participated in this study. The results of the study indicate that the development policy in Limboto Lake shows progress, but still faces challenges such as increasing responsiveness and coordination between stakeholders, weak coordination, long bureaucracy, and minimal supervision. Although the adequacy and accuracy of the policy are quite fulfilled, the implementation is not optimal, especially in the distribution of benefits and ecosystem protection. Conclusion: The development policy in Lake Limboto shows progress, but still faces challenges in coordination, implementation, and distribution of benefits, so it is necessary to improve the effectiveness and responsiveness indicators. Suggestions: the government needs to improve the accuracy, distribution, responsiveness, efficiency, and effectiveness of the policy by focusing on critical areas, coordination, and optimal communication.